DEVELOPMENT OF ENGLISH READING COMPREHENSION SKILLS USING SCAFFOLDING TECHNIQUE FOR MATHAYOMSUKSA 4 STUDENTS - Pimpan, Pakpilai; Thipatdee, Goachagorn; Thongchalerm, Sirisuda (Journal of Graduate School Sakon Nakhon Rajabhat University, 2025)
The purposes of this study were 1) to develop learning activity packages for English reading comprehension using scaffolding technique for Mathayomsuksa 4 students with the required efficiency of 80/80; 2) to examine and compare English reading comprehension skills before and after using scaffolding technique for Mathayomsuksa 4 students; and 3) to investigate the satisfaction of the students with English reading comprehension activities using scaffolding technique for Mathayomsuksa 4 students. The sample was 30 Mathayomsuksa 4 students at Amnatcharoenpittayakom School in the first semester of 2024, selected by cluster sampling. The research instruments were 12 reading activity packages, a 40-item test assessing English reading comprehension skills, and a 20–item survey measuring student satisfaction with the developed learning management. The statistics were mean, percentage, standard deviation, the effectiveness index, and the t–test for Dependent Samples. The research findings were as follows: 1) The package efficiency values were 83.00/83.92, which exceeded the established criteria of 80/80; 2) The English reading comprehension skills of Mathayomsuksa 4 students were higher than those before the intervention at the .01 level of significance, with an increase of 75.75 at a higher level. and 3) The satisfaction of Mathayomsuksa 4 students with the developed learning management was overall at the highest level. ( = 4.67 และ S.D. = 0.58)